2017
DOI: 10.4018/978-1-5225-2203-4.ch010
|View full text |Cite
|
Sign up to set email alerts
|

Public Procurement Framework in India

Abstract: Studies highlight that public procurement in any country acts as a barometer of public confidence in fairness and transparency of public institutions. A number of cases related to corruption in public procurement in the country have been highlighted by media on regular basis. These incidents raise questions regarding robustness of the procurement framework in vogue in the country. Though no special legislative framework dealing with public procurement exists in the country, the administrative guidelines on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…However, 17.6% of the respondents disagreed and 10.6% strongly disagreed on the same implying that information sharing between the firm and suppliers to some extents promoted competitive bidding thereby improving on service delivery. These results are in agreement with Panda, Sahu and Gupta (2010) who revealed that e-procurement system eliminates malpractices as it enhance transparency and probity by keeping a traceable online electronic record of transactions. On a further note, e-procurement benefits includes reduction of process time and cost, improved service level, increased efficiency, increased customer satisfaction, openness and transparency, increased economic competitiveness.…”
Section: 37supporting
confidence: 91%
“…However, 17.6% of the respondents disagreed and 10.6% strongly disagreed on the same implying that information sharing between the firm and suppliers to some extents promoted competitive bidding thereby improving on service delivery. These results are in agreement with Panda, Sahu and Gupta (2010) who revealed that e-procurement system eliminates malpractices as it enhance transparency and probity by keeping a traceable online electronic record of transactions. On a further note, e-procurement benefits includes reduction of process time and cost, improved service level, increased efficiency, increased customer satisfaction, openness and transparency, increased economic competitiveness.…”
Section: 37supporting
confidence: 91%
“…Several studies have been undertaken on transparency in public procurement (Panda et al, 2010;Siahaan and Trimurni, 2014). According to the World Trade Organization, transparency involves three main requirements: to make information on relevant laws, regulations and other policies publicly available; to notify interested parties of relevant laws and regulations and changes to them; and to ensure that the laws and regulations are administered in a uniform, impartial and reasonable manner (Bellver and Kaufmann, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%